Talitrid crustaceans (Amphipoda - Talitridae) from Vietnam sea - Thanh, Dang Ngoc; Anh, Le Hung (Academia Journal of Biology, 2012)
Based on the taxonomical study on materials collected from different localities in the nearshore waters of Vietnam for a long times, 6 species of amphipods be longing to Talitridae group were found, all are new for the Vietnam Sea, of those, 1 new genus Vietorchestia gen. nov. and three new species Platorchestia vietnamica sp. nov., Floresorchestia vugiaensis sp. nov., Vietorchestia quadrata sp. nov. are descrilied and illustrated. Platorchestia vietnamica sp. nov. (Figs 1 - 15) Head with large, round eyes. Antenae 1 with 3-jointed peduncle, the 2nd the longest, Flg 5 articulate. Ant 2 with 5th peduncular article longer than 4th article. Gnathopod 1 (male) with slender 5th article, cylindrical in form with tumescent humps at posterodistal angle. Gnathopod 2 with subround 6th article, palm occupied nearly 1/2 posterion margin, palmar margin with rows of spines and setae. Uropods 1 - 2 normally structured. Uropod 3 with rami subepual in length with infllated peduncule parts. Telson apically notched, each lobe with distal rows of spines. Female with clearly different dimorphism structure in gnathopods 1 and 2. Floresorchestia vugiaensis sp. nov. (Figs 16 - 27) Head anterodistal margin straigth, eyes very large. Ant 1 reaching to distal margin of 4th peduncular article of antenae 2. Ant 1 peduncular article subequal in lenth, Flg 3-jointed. Ant 2 with short 4th article, half length of 5th article as long as, Flg 17-jointed. Gnathopod 1 (male) with 6th article 1/5 5th article as long as, posterodistal angle of the 2 articles with tumescent humps. Gnathopod 2 with short 5th article, 6th larger, eggshaped, palm oblique, with a medial wide shallow excavation delimited by strong toothed tumescent hump. Dactylus strongly claw like, with a melial tubercle cocrespound with medial palm excavation. Uropod 1 - 2 distal part bearing calceolus. Uropod 3 with larger peduncular part, rami subequal in length with peduncle. Telson bilobed in shape. Female with dimorphism in gnathopods 1 and 2 structures. Vietorchestia gen. nov. Eyes very large, subquadrate, antenae 1 short, flagellum 5-jointed. Antenae 2 long, 5th peduncular article 2 times as long as in length of 4th article, flagellum 18 - 20-jointed. Gnathopod 1 (male), 5th and 6th article with tumescent humps at posterodistal angle gnathopod 2 short, 6th article subquadrate in shape, palm slightly oblique, delimited externally by a strong tooth. Uropod with rami finger form, longer than peduncle part. Epimera 1 - 3 posterodistal angles untoothed. Typ species: Vietorchestia quadrata sp. nov. Vietorchestia quadrata sp. nov. (Figs 28 - 41) Eyes very larger, quadrate. Ant 1 short, peduncle 3-jointed, the 2nd the longest, flagellum 5-jointed. Ant 2 long, 5th peduncular article 2 times as long as 4th article, flagellum 18-jointed. Gnathopod 1 (male) with 5th article 2 times as long as 6th article posterodistal angle of the 2 articles with tumescent humps. Gnathopod 2 rather short, 6th article quadrate, palm slightly oblique, delimited externally by a strong tooth. Palm margin with a rows of spines. Pereopods 3 - 7 with normal structures. Uropod 3 with inflated peduncle part, rami finger form, shorter than peduncle. Telson bilobed, distally notched. Epimera 1 - 3 with posterodistal angles untoothed.